Realizing Saudi Vision 2030 (Bloomsbury Publishing (UK), 2026)
All too often, Saudi Vision 2030 is associated outside the Kingdom solely with mega-projects such as ‘Neom’ and ‘The Line’. But how the Vision is being realized through ‘real life’ situations and issues is frequently overlooked. This open access book is a behind-the-scenes investigation into the current transformations taking place in Saudi Arabia. It comprises contributions from academics, researchers, policymakers and practitioners who have access to the decision-makers and relevant institutions in the country. Based on these authors’ extensive experiences and this unique access, chapters focus on the remodelling of government entities, the creation of institutions, and the new opportunities made available for Saudis through human capital development initiatives, all key issues that are central to the Vision. In assessing the transformations taking place in Saudi Arabia, this book is a much-needed evaluation into how Vision 2030 is being successfully implemented and what factors challenge development. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the King Faisal Center for Research and Islamic Studies.